Reconstruction of the Concept of Morals of KH. Bisri Mustofa Rembang to Support the Achievement of SDGs Education Quality - Aly Mashar; Kholis Firmansyah; Zaid Munawar; Muhammad Wael Chafoory (Profetika: Jurnal Studi Islam, 2025)
Objective: This research aims to examine the intellectual biography of KH. Bisri Mustofa, explore the background and format of his moral writings, and analyze the moral concepts in his works in relation to the categorization of moral textbooks used in Islamic Religious Higher Education Institutions (PTKI). This study also positions his contributions in the context of achieving SDG 4: Quality Education through culturally relevant moral education. Theoretical framework: The study employs an interpretive descriptive approach, combining Islamic education theory and classical moral concepts, supported by theoretical triangulation to ensure data validity. The framework emphasizes the alignment between traditional Islamic scholarship and contemporary educational goals within the SDGs framework. Literature review: The review includes the biography of KH. Bisri Mustofa, an exploration of Arabic Pegon Jawi texts, Islamic perspectives on morality, and the structural categorization of moral textbooks in PTKI. It highlights the underutilized richness of traditional Javanese Islamic literature in current moral pedagogy. Methods: Utilizing a library research method, the study collects data through documentation, processes it through content analysis, and validates findings via theoretical triangulation. Results: KH. Bisri Mustofa emerges as a multidimensional intellectual whose moral books—Ngudi Susila, Mitra Sejati, and Washaya—comprehensively address all major categories of moral education within PTKI, including an additional, rarely discussed dimension: morality in the teaching and learning process. His Al-Ibriz complements these by emphasizing moral obligations to Allah and the Prophet. Implications: This research underscores the relevance of integrating classical Nusantara Islamic texts into the modern PTKI curriculum as a strategy for enhancing moral education aligned with the goals of SDG 4, promoting inclusive, equitable, and culturally grounded learning environments. Novelty: The study presents a novel curriculum-oriented analysis of Arabic Pegon moral texts and maps their suitability to the moral education framework of PTKI. It also identifies a new thematic dimension—educational morality—that is often overlooked in mainstream textbooks.